2015
DOI: 10.1080/23324309.2015.1060245
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Spatial Discretization Error of Thermal Emission in Implicit Monte Carlo Simulations

Abstract: Implicit Monte Carlo simulations of thermal radiative transport can exhibit what is known as teleportation error in problems with strong coupling between radiation and matter. Teleportation error occurs when energy deposited in a localized region of a spatial zone is emitted throughout the zone in the next time step. Teleportation error is commonly reduced by biasing the positions of photon thermal emission using a fit to the spatial distribution of temperature to the fourth power. The current work samples and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 5 publications
0
43
0
Order By: Relevance
“…To be more precise, in this paper, we are even interested in being able to accurately capture a particular regime: in diffusive media, system (1) 4π dω = aT 4 m and Φ r (T r ) = aT 4 r , the second equation is equivalent to T m = T r : the radiative and matter temperatures are at equilibrium. In the above equation, δ ∼ 0 is a small parameter characterising what is commonly called the equilibrium 1 diffusion 2 limit [2,3,4]. The limit can be defined by introducing a characteristic length X , a characteristic time T and a characteristic collision rate λ and assuming we have…”
Section: Introductionmentioning
confidence: 99%
“…To be more precise, in this paper, we are even interested in being able to accurately capture a particular regime: in diffusive media, system (1) 4π dω = aT 4 m and Φ r (T r ) = aT 4 r , the second equation is equivalent to T m = T r : the radiative and matter temperatures are at equilibrium. In the above equation, δ ∼ 0 is a small parameter characterising what is commonly called the equilibrium 1 diffusion 2 limit [2,3,4]. The limit can be defined by introducing a characteristic length X , a characteristic time T and a characteristic collision rate λ and assuming we have…”
Section: Introductionmentioning
confidence: 99%
“…Using particle histories to aid in construction of the source tilts is seen to further mitigate teleportation error relative to standard linear tilts in T 4 . It seems, though, that using particle histories to construct the tilt may further couple MC noise into the simulation and may also be prohibitive with respect to memory (Irvine et al, 2011;Smedley-Stevenson and McClarren, 2015). With varying difficulty, these tilt schemes are extensible to multiple dimensions.…”
Section: Source Tilting Reviewmentioning
confidence: 96%
“…Consequently, for thermal waves, energy appears to "teleport" at non-physical speed to downstream cell locations (McKinley et al, 2003). Because it is often not computationally practical to introduce spatial grids that resolve mean-free-path length scales, effort has been made to mitigate teleportation error heuristically with material properties (i.e., temperature) (Fleck and Canfield, 1984;Cheatham, 2010;Irvine, Boyd, and Gentile, 2011;Urbatsch and Wollaber, 2011;Smedley-Stevenson and McClarren, 2015).…”
Section: Source Tilting Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…To reduce teleportation error without relying on an interpolation of the temperature grid or functional form of the previous absorption locations, Irvine et al suggested storing particle absorption locations and ensuring that particles in the ensuing cycle sample their emission locations among the absorption locations from the previous cycle (Irvine, 2013;Irvine, Boyd, and Gentile, 2015). In the KULL ICF code (Rathkopf et al, 2000), Irvine reported enhanced accuracy for coarser spatial zoning at a relatively modest (25%) increase in memory usage for 3D problems and about a 13% decrease in compute time.…”
Section: Teleportation Errormentioning
confidence: 99%